Plasticity of T helper cell subsets: Implications in periodontal disease - Avaneendra Talwar; K V Arun; T. S. S. Kumar; Jasmine Clements (Wolters Kluwer Medknow Publications, 2013)
T helper (Th) cells have an important role in host defence as well in the pathogenesis of periodontal disease. Th cells differentiate from naive cells into various subsets, each of which is associated with a set of inducing and effector cytokines. Previously, it was thought that this differentiation was an irreversible event. Recent evidence suggest that even differentiated Th cells, retain the flexibility to transform from one lineage to another, a phenomenon referred to as plasticity. This plasticity is thought to be brought about by epigenetic modifications that are regulated by external and internal signals in the micro-environment of these cells. The factors and mechanisms which affect the plasticity of these cells and their potential role in the etio-pathogenesis of periodontal disease has been described in this article.